REPRESENTATION OF GENDER IN MULAN 2020 : A SEMIOTICS APPROACH - Puan Suri Mira Annisa; Elisa Betty Manullang (Jurnal Darma Agung, 2022)
Movie is a work of art as a communication medium that can convey a message to many people. This paper contains some important information related to the understanding of Chinese culture towards Mulan as a strong woman through a movie called Mulan, the 2020 version directed by Niki Caro. This study aims to analyze, interpret and represent the gender of the main character in the movie, namely Mulan, through a semiotic approach guided by Pierce's theory. In addition, it has also been briefly explained the storyline of the movie, especially the focus on Mulan. The research method used by the researchers was a qualitative discourse analysis approach and was developed textually. This includes analyzing the discourse text contained in Mulan's movie based on her character as feminine under gender code and then connecting it with social life, analyzing body language or cultures conveyed by each scene that can describe Mulan's character as a great woman. Then, the data source has been collected online, that is from the internet and this article is a non-participant. Based on the movie's story, there are 10 valid data that have been captured as evidence of social impact. The data was analyzed through the Mulan movie, which has a duration of 1 hour 55 minutes, with the themes of adventure, drama, action. Meanwhile, findings and discussion was focused on analyze the movies based of the characters, gender and based of semiotics approach with showing some evidences in the form of pictures of the scene that showed that the women gender in the Mulan movies.This article concluded that gender representation in the Mulan movie 2020 is a serious problem that occurs in the socio-cultural environment of society, so the use of the Semiotics approach helps in analyzing the gender context in the movie.